Analisis Keputusan Dan Metode Penghakiman Terhadap Pemberian Wasiat Wajibah Kepada Anak Tidak Sah Taraf Dalam Kes No. 0257/ Pdt.G/2012/PA. Jbg: An Analysis of Decision and Method of Judgment toward Granting Wajibah Will to the Illegitimate Children in the Case Number 0257 / Pdt.G / 2012 / PA. Jbg - Muhammad Daud, Zakiul Fuady; Azahari, Raihanah (Jurnal Fiqh, 2020)
Children born from illegitimate marriages have a legal impact including inheritance issues. In Islamic perspective, he only inherited from his mother and his mother’s family and did not inherit from his biological father. In this case the judge sometimes gives the wajibah will and sometimes not. This study aims to describe the decisions and methods of judgement in the case of illegitimate children and analyze them in the Shariah perspective. This qualitative study combines empirical studies (law in action) with normative legal studies (law in book) by making judges as respondents. Data collection techniques are carried out through interviews and documentation, while data analysis uses data reduction, data display and conclusion. The results showed that the judge gave the wajibah will to illegitimate children by using the method of extensive interpretation and revoked the grant given to him together with the defendant using the argumentum a contrario method. In the perspective of Shariah, the judge’s decision was inappropriate because revoking the grant instead gave wajibah will that is still debatable.